Role of Amniotic Membrane Graft in the Management of Corneal Ulcer in a Tertiary Care Hospital in Peshawar - Ali, Palwasha; Karim, Samina (Biological and Clinical Sciences Research Journal, 2025)
Corneal ulcers are a significant cause of visual morbidity and, if inadequately treated, may lead to corneal scarring or perforation. Amniotic membrane grafting has emerged as an effective therapeutic option due to its anti-inflammatory, anti-fibrotic, and epithelial healing properties. However, local data regarding its efficacy remains limited. Objective: To determine the efficacy of amniotic membrane grafting in the management of corneal ulcers at a tertiary care hospital in Peshawar. Methods: This descriptive study was conducted at a tertiary care hospital in Peshawar and included 139 patients aged 18–60 years of either gender presenting with corneal ulcers. A corneal ulcer was defined as involvement of more than 50% of the corneal depth, dry eye, and confirmed bacterial growth. Patients with glaucoma, chronic dacryocystitis, or corneal ulcers associated with entropion were excluded. All patients underwent amniotic membrane grafting, and treatment efficacy was assessed at eight weeks post-procedure. Data were analyzed using SPSS version 26, and outcomes were reported as frequencies and percentages. Results: A total of 139 patients were enrolled, with a mean age of 46.91 ± 13.54 years and a mean body mass index of 24.45 ± 1.89 kg/m². There were 74 (53.2%) male and 65 (46.8%) female patients. Successful treatment outcomes were achieved in 121 patients, yielding an overall efficacy rate of 87.1%. Conclusion: Amniotic membrane grafting demonstrated high efficacy in the management of corneal ulcers, with a success rate of 87.1%. This technique appears to be a safe and effective therapeutic option for treating corneal ulcers and may help reduce disease-related morbidity when applied appropriately.